Advances of stable isotope technology in food safety analysis and nutrient metabolism research. (15th May 2023) - Xia, Wei; Fang, Xiangjun; Gao, Yuan; Wu, Weijie; Han, Yanchao; Liu, Ruiling; Yang, Hailong; Chen, Hangjun; Gao, Haiyan
Highlights: Systematically reviewed stable isotope (SI) dilution technology in food safety analysis. Advance of SI tracer in nutrients metabolism research is discussed. Proposed some future prospects for SI in food analysis and nutrients metabolism. Abstract: Food quality, safety, and the regulatory metabolism of food nutrients in cells are primary factors in determining human health. However, residues of undesirable or hazardous compounds in food products and dysregulation in the nutrient metabolism inevitably occur occasionally. For years, chromatography-mass spectrometry technology has been recognized as an essential research tool in food analysis and nutrient metabolism research, and it is more accurate and robust when coupled with stable isotopes. In this study, we summarize the applications of stable isotope technology in the quantification of contaminant residues (pesticides, veterinary drugs, mycotoxins, polycyclic aromatic hydrocarbons, and other hazardous compounds) in foods and in the nutrients (glucose, lipids, amino acids and proteins) metabolism research. The aim of this review was to serve as a reference for providing effective analysis techniques for protecting food quality and human health, and to pave the way for the broader application of stable isotope technology.